“The One about Coyote going West”: mimesis and ethics in multicultural literary landscapes of Canada and Australia - Polak, Iva (2010)
The paper focuses on the so-called appropriation of indigenous voice and/or subject appropriation (Young/Haley) in a literary space of the two multicultural postcolonial locations, Canada and Australia. Contributing to a very uneasy palimpsest of postcoloniality, this appropriation will be discussed against the concept of a literary work as a construct of a possible world (mimesis), i.e. the space of textual freedom ; postcolonial space which is multicultural and “hybrid”, i.e. the space of cultural diversity ; and finally ethics which sets boundaries to the possible worlds of literature by challenging an often easy-going assumption of postcolonial “hybridity”. The implications of “Natives and AlterNatives” (Smyth Groening) will be discussed against the backdrop of the complexities of cultural appropriation (J. O. Young, M. Nolan, C. Dawson), the “niche” of Indigenous literature and Indigenous book market (A. M. Heiss), the notion of “glocal” texts (D. Riemenschneider), and various views coming from Canadian and Australian Indigenous literati and scholars. Special space is reserved for the comments by the two Signifying Monkeys: Coyote (T. King) and Da (B. Pascoe).
Projekt MZOS
ENG